2012
DOI: 10.1016/j.biopha.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive sphingolipids in docetaxel-induced apoptosis in human prostate cancer cells

Abstract: In this study, we examined the possible roles of ceramide/sphingosine-1-phosphate and ceramide/glucosyleceramide signaling in docetaxel-induced apoptosis by examining expression levels of the glucosyleceramide synthase and sphingosine kinase-1 and ceramide synthase gene family. As confirmed by isobologram analysis, docetaxel in combination with agents that increase intracellular ceramide levels increased the cytotoxic and apoptotic effects of docetaxel synergistically. More importantly, RT-PCR results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…According to our studies, SKi increases the cytotoxic effects of dasatinib on K-562 and Meg-01 human chronic myeloid leukemia cells [118]. It has also been reported that there are synergistic cytotoxic and apoptotic effects between PDMP and docetaxel on DU-145 and PC-3 human prostate cancer cells [119].…”
Section: Sphingosine Kinase Inhibitorssupporting
confidence: 59%
See 3 more Smart Citations
“…According to our studies, SKi increases the cytotoxic effects of dasatinib on K-562 and Meg-01 human chronic myeloid leukemia cells [118]. It has also been reported that there are synergistic cytotoxic and apoptotic effects between PDMP and docetaxel on DU-145 and PC-3 human prostate cancer cells [119].…”
Section: Sphingosine Kinase Inhibitorssupporting
confidence: 59%
“…In one of our studies we found that the sensitivity of human chronic myeloid leukemia cells increased to nilotinib via coadministration of C8-ceramide [117]. Combination of C:8 ceramide increased the antiproliferative and apoptotic effects of resveratrol on chronic myeloid leukemia [114] and acute myeloid leukemia [115] cells while combination of docetaxel with C8:ceramide showed significant synergistic apoptosis on prostate cancer cell lines [119]. In a recent report, Zhu et al [191] investigated the synergistic effects of histone deacetylase inhibitor, TSA, and C6ceramide both in vitro and in vivo pancreatic and ovarian cancer models.…”
Section: C16-serinol Lc 124mentioning
confidence: 62%
See 2 more Smart Citations
“…Our group has also shown that the inhibition of GCS with PDMP increased anti-proliferative and apoptotic effects of imatinib [86], nilotinib [87], and dasatinib [88] on chronic myeloid leukemia cells synergistically. GCS inhibition causes enhanced cytotoxic and apoptotic responses in human prostate cancer cells in response to docetaxel treatment [89]. It was also demonstrated that inhibition of GCS reversed resistance to doxorubicin and vincristine in leukemia [90,91].…”
Section: Glucosylceramide Synthase In Cancer Therapymentioning
confidence: 99%